Uma seção plural - Frochtengarten, Janete (Percurso, 2005)
The author of the first book review published in Percurso (see below) reflects on the double contribution that the section – which has presented some two hundred books since 1988 – has been offering to Brazilian analysts and to the public in general: information about the growing number of good works that appear every year, and formation of the reader, an effect that comes from the mobilization and association the texts published in the section strive to stir in the reader.